Histological and clinical disease progression in patients with metabolic dysfunction-associated steatotic liver disease using paired liver biopsy - Ekelik, Merve; Gokce, Dilara Turan; Gumussoy, Mesut; Kiremitci, Saba; Bodakci, Emin; Yilmaz, Volkan; Idilman, Ramazan (Elsevier, 2024)
[Abstract Not Available]
European-Association-for-the-Study-of-the-Liver Congress (EASL) -- JUN 05-08, 2024 -- Milan, ITALY